KEPENTINGAN POLITIK PEMERINTAHAN MU’AWIYAH BIN ABU SUFYAN: PERPINDAHAN KEKUASAAN DARI KUFAH KE DAMASKUS - Nurus Syarifah (Fakultas Syari'ah Universitas Islam Negeri Fatmawati Sukarno Bengkulu, 2021)
Abstract: This article explains about the events of political interest that occurred during the time of Ali bin Abi Thalib, from the murder of Utsman bin Affan to move of power to Damascus by Muawiyah bin Abu Sufyan. The method used in this research is descriptive analytical method. This method is used to map the discussion and answer the question why Mu'awiyah chose Damascus as the center of his power and what was the reason to move? After conducting the research, it can be concluded that the conflict between Ali bin Abu Talib and Muawiyah bin Abu Sufyan was based on the failure of Ali bin Abi Talib to reveal the case of Utsman bin Affan. This failure triggered domestic political turmoil due to Muawiyah's disapproval of Ali's performance, which seemed to have taken the case seriously. The Shiffin war incident became the entrance for Muawiyah to overthrow Ali bin Abi Talib. Tahkim, which could be expected as a solution to the conflict, actually became a loss for Ali and left the leadership to his son, Husein. Muawiyah's soft power strategy to coup Husein went smoothly. After he assumed control as caliph, Muawiyah moved the center of power to Damascus. This is because Damascus is a strategic area and can provide benefits for the caliphate of Muawiyah bin Abu Sufyan.Keywords: Political Interests; Mu'awiyah bin Abu Sofyan; Ali bin Abi Thalib; Damascus